2008
DOI: 10.1103/physrevb.77.195411
|View full text |Cite
|
Sign up to set email alerts
|

Average density of states in disordered graphene systems

Abstract: In this paper, the average density of states (ADOS) with a binary alloy disorder in disordered graphene systems are calculated based on the recursion method. We observe an obvious resonant peak caused by interactions with surrounding impurities and an anti-resonance dip in ADOS curves near the Dirac point. We also find that the resonance energy (Er) and the dip position (ε dip ) are sensitive to the concentration of disorders (x) and their on-site potentials (v). An linear relation, ε dip =xv, not only holds w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 44 publications
3
21
0
Order By: Relevance
“…The presence of the substrate greatly increases the possibility to introduce various defects into graphene. For example, in the graphene deposited on silicon, vacancies can occur [13,14], whereas in graphite (a set of weakly interacting graphene monolayers) vacancies heal and form a stacking fault with local fivefold symmetry axis [15]. Impurity atoms embedded in graphene may lead to the appearance of impurity states outside the band of quasi-continuous spectrum.…”
Section: Impurity Levels In the Electron Spectra Of Graphenementioning
confidence: 99%
“…The presence of the substrate greatly increases the possibility to introduce various defects into graphene. For example, in the graphene deposited on silicon, vacancies can occur [13,14], whereas in graphite (a set of weakly interacting graphene monolayers) vacancies heal and form a stacking fault with local fivefold symmetry axis [15]. Impurity atoms embedded in graphene may lead to the appearance of impurity states outside the band of quasi-continuous spectrum.…”
Section: Impurity Levels In the Electron Spectra Of Graphenementioning
confidence: 99%
“…The changes of the ADOS near the charge neutrality point (NP) still remain ambiguous and under debate3456789. One of the theoretical predictions on disordered graphene suggested that the ADOS followed a power law, i.e.…”
mentioning
confidence: 99%
“…Furthermore, abundant carbons in radical form may also inhibit the loss of carbon atoms from the frameworks during the heat treatment to remove oxygen-containing groups. [102] The stability of the electrode is important for solar cells. Zhao et al demonstrated the excellent stability of solar cells with graphene electrodes.…”
Section: Transparent Electrodesmentioning
confidence: 99%